2021
DOI: 10.3389/fchem.2021.682404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Low Cost Titanium Silicalite-1 Zeolite for Highly Efficient Propylene Epoxidation

Abstract: Developing an effective and low-cost system to synthesize titanium silicalite-1 (TS-1) zeolite is desirable for a range of industrial applications. To date, the poor catalytic activity of the synthesized zeolite due to the low amount of framework titanium and large crystal size is the main obstacle limiting the widespread application of this material. Moreover, a large amount of wastewater is often produced by the existing synthesis process. Herein, a green and sustainable route for synthesizing small-crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“… 228 Some recent studies showed that the graded TS-1 obtained after alkali etching has higher catalytic activity for propylene epoxidation, and the turnover frequency is as high as 1650h −1 . 256 …”
Section: Ts-1 Catalyst Design For Efficient Catalytic Performancementioning
confidence: 99%
“… 228 Some recent studies showed that the graded TS-1 obtained after alkali etching has higher catalytic activity for propylene epoxidation, and the turnover frequency is as high as 1650h −1 . 256 …”
Section: Ts-1 Catalyst Design For Efficient Catalytic Performancementioning
confidence: 99%
“…Liu et al synthesized TS-1 using TiCl 3 , TBOT, and Ti(SO 4 ) 2 as titanium sources, TPABr as the template agent, ethanolamine as the alkaline source, and vapor-phase silica as the silicon source. 70 The mixed sol gel prepared with TBOT as the titanium source, had the relative crystallinity and framework titanium content of the TS-1 due to its higher alkalinity. The TS-1 synthesized with TBOT as the titanium source showed the highest epoxidation selectivity for propylene epoxidation.…”
Section: Coordination Number Of Ti Active Sitesmentioning
confidence: 99%
“…Therefore, in this system, using Ti­(SO 4 ) 2 as the titanium source can restrain the formation of nonframework titanium species, thus increasing the content of framework titanium species and further exhibiting the highest epoxidation yield (99.04%) in chloropropene epoxidation. Liu et al synthesized TS-1 using TiCl 3 , TBOT, and Ti­(SO 4 ) 2 as titanium sources, TPABr as the template agent, ethanolamine as the alkaline source, and vapor-phase silica as the silicon source . The mixed sol gel prepared with TBOT as the titanium source, had the relative crystallinity and framework titanium content of the TS-1 due to its higher alkalinity.…”
Section: Direct Regulation Of Ti Active Sitesmentioning
confidence: 99%